Improvement in Body Posture of Sumedang Tofu Small Enterprise Workers Using Workplace Ergonomic Risk Assessment (WERA) - Siska, Merry; Harahap, Aisyah Aulia (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2022)
Abstract This study aims to analyse the work body postures, to determine the work risk level before and after the improvement using the Workplace Ergonomic Risk Assessment (WERA) and to improve the workstation by designing ergonomic production tools. An empirical study was carried out at a small industry producing Sumedang Tofu at Rimbo Panjang, Pekanbaru, Indonesia. The workers must bend their body to move 77 kg soybeans with an 11 kg single-lifting capacity. The level of work risk was determined using the Workplace Ergonomic Risk Assessment (WERA) method based on nine categories, i.e., shoulders, wrists, back, legs, neck, strength, vibration, contact pressure, and work duration. The soaking and milling stations scored 35 and 31 using the WERA method. The two scores indicated an average performance level that requires improvement. Anthropometric data were used to develop tools for improving workers' body posture. The new tool used for soaking and milling has footrests, so workers did not have to reach too far above their chests to move the soybeans to the milling. The soaking station and the milling station both achieved a score of 24, which is considered as a low level, indicating that neither station requires improvement. Time reduction after the body posture improvement was 3.33 seconds for the milling station and 2.08 seconds for the soaking station.Keywords: anthropometry, soybean, posture improvement, workplace ergonomic risk assessment AbstrakPenelitian ini bertujuan untuk mengidentifikasi postur kerja untuk mengetahui tingkat risiko kerja sebelum dan sesudah dilakukan perbaikan menggunakan metode Workplace Ergonomic Risk Assessment (WERA) dan memperbaiki workstation dengan merancang alat produksi yang ergonomis. Sebuah studi empiris dilakukan di sebuah usaha kecil tahu Sumedang di Rimbo Panjang, Pekanbaru, Indonesia. Para pekerja perusahaan harus membungkuk untuk memindahkan 77 kg kedelai dengan kapasitas angkat 11 kg. Tingkat risiko kerja ditentukan dengan menggunakan metode Workplace Ergonomic Risk Assessment (WERA) berdasarkan sembilan kategori, yaitu bahu, pergelangan tangan, punggung, kaki, leher, kekuatan, getaran, tekanan kontak, dan durasi kerja. Stasiun perendaman dan stasiun penggilingan memperoleh skor 35 dan 31 dengan menggunakan metode WERA sebelum perbaikan postur tubuh. Kedua skor tersebut menunjukkan tingkat kinerja rata-rata yang memerlukan perbaikan. Data antropometri digunakan untuk mengembangkan alat untuk memperbaiki postur tubuh pekerja. Alat baru yang bisa digunakan untuk merendam dan menggiling ini memiliki pijakan kaki, sehingga pekerja tidak perlu menjangkau terlalu jauh di atas dada untuk memindahkan kedelai ke penggilingan. Stasiun perendaman dan stasiun penggilingan keduanya mencapai skor 24, dengan tingkat yang rendah, menunjukkan bahwa tidak ada stasiun yang memerlukan perbaikan. Pengurangan waktu setelah perbaikan postur tubuh adalah 3,33 detik untuk stasiun penggilingan dan 2,08 detik untuk stasiun perendaman.Keywords: anthropometri, kedelai, perbaikan postur, workplace ergonomic risk assessment